Effect of Summer forage crops and phosphogypsum-enriched urea on soil quality, nitrogen-use efficiency and quality of Basmati rice (Oryza sativa) and their residual effect on succeeding wheat (Triticum aestivum) - BANA, R S; SHIVAY, Y S; TYAGI, V K (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during 2007-08 and 2008-09 at New Delhi to study the effect of summer forage crops, pearlmillet [Pennisetum glaucum (L.) R. Br. emend. Stuntz] and cowpea [Vigna unguiculata (L.) Walp.] and phosphogypsum-enriched urea (PGEU) on soil quality, nitrogen-use efficiency, quality parameters and yield of Basmati rice (Oryza sativa L.) and their residual effect on succeeding wheat (Triticum aestivum L. emend. Fiori & Paol.) productivity under Basmati rice–wheat cropping system. Among the 3 forage crops grown during summer, pearlmillet + cowpea mixture recorded significantly higher fodder yields, i e 43.2 and 42.7 tonnes/ha green fodder during 2007 and 2008, respectively compared to pearlmillet sole and cowpea sole. In Basmati rice, soil quality, nitrogen-use efficiency, yield and quality parameters of Basmati rice were increased significantly due to preceding forage crops. Based on mean of 2 years data, application of 7.5% PGEU significantly increased rice yield (20.5%) and rice kernel quality parameters, viz. protein content (19.9%), hulling (11.4%) and milling (12.5%), head rice recovery (12.5%), rice grain length before (3.5%) and after cooking (6.8%) and rice grain breadth before (8.6%) and after cooking (5.5%) of Basmati rice than 0% PGEU. Significantly higher yield, i e 5.33 tonnes/ha and 5.55 tonnes/ha during 2007 and 2008 respectively and better quality parameters, viz. hulling, milling and head rice recovery of Basmati rice was obtained when it was grown after the harvest of cowpea than the other treatments. Application of 7.5% PGEU resulted in good quality Basmati rice with increased yield. Different summer forage crops and PGEU applied to Basmati rice left significant residual effect on succeeding wheat yield under Basmati rice–wheat cropping system.